CONNECTIVITY, MULTI-LITERACIES, SKILLS AND COMPETENCIES: THE CHANGED CONTEXTS OF ONLINE TEACHING AND LEARNING - Terblanché, Elize (DIRASAT: EDUCATIONAL SCIENCES, 2016)
ملخص تعالج هذه المقالة ظروف التعلم الالكتروني و تعليمه. و هذه الظروف تتغيرة من حين إلى أخر. من أهداف هذه المراجعة أن تستكشف و تصف تطوير المهارات المفاهيمية و المهارات تتعلق بمناهج التعلم المتعددة الجديدة. و من نتائج دراستنا أن يجتمع الخبراء على أن لا تستبعد الأعمال الرقمية من التعليم. و أيضاً أن الطلاب الذين يشاركون في التكنولوجيا يشكلون الاتحادات على انترنت. و هم أيضاً يربطون عالمياً وبذلك يصنعون العلم الجديد. تمكن النماذج المفاهيمية الحاضرة على الانترنت تحويل مهارات قرن إحدى وعشرين إلى التعلم الالكترني. و تعتبر هذه المقالة أيضاً التحديات التي تواجه الطلاب و المعلمين في الظروف المختلفةThis article addresses the changing contexts of e-learning and teaching. Objectives of this purposive literature survey are to explore and describe the development of conceptual and multi-literacy skills. Findings reveal consensus that digital practices cannot be excluded from teaching; that students who have espoused technology are forming online associations and are connecting globally to create new knowledge. Existing online conceptual models enable the transformation of 21st century skills into e-learning. The article also considers challenges faced by students and facilitators under different circumstances. A pertinent need identified in an African context is the availability of online content in local languages.